One-stage hybrid coronary revascularization for the treatment of multivessel coronary artery disease— Periprocedural and long-term results from the “HYBRID-COR” feasibility study - Sanetra, Krzysztof; Buszman, Piotr Paweł; Jankowska-Sanetra, Justyna; Cisowski, Marek; Fil, Wojciech; Gorycki, Bogdan; Bochenek, Andrzej; Slabon-Turska, Monika; Konopko, Marta; Kaźmierczak, Paweł; Gerber, Witold; Milewski, Krzysztof; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The constant growth of interest in hybrid coronary artery revascularization (HCR) is apparent. Yet, few studies report outcomes of the one-stage HCR. Consequently, the status of such procedures is not adequately supported in clinical guidelines. The aim of this study was to report safety, feasibility and long term-outcomes of the one-stage HCR. Methods and Results: Patients were enrolled into the prospective one-stage hybrid coronary revascularization program (HYBRID-COR). They underwent one-stage hybrid revascularization procedure whilst on double antiplatelet therapy (DAPT) with Ticagrelor: endoscopic atraumatic coronary artery bypass grafting (EACAB) for revascularization of left anterior descending (LAD) artery and percutaneous intervention in non-LAD arteries with contemporary drug eluting stents. The composite primary endpoint included MACCE (major adverse cardiac and cerebrovascular events: death, myocardial infarction, stroke, repeat revascularization) in a long-term observation. The study cohort consisted of 30 patients (68% male) with stable coronary artery disease (26.7%) and unstable angina (73.3%). Procedural success was 100%. No death, myocardial infarction (MI) or stroke were observed in the perioperative period. One patient (3.3%) required chest revision and blood transfusion due to surgical bleeding. Kidney injury was noted in 2 patients (6.6%). In a long term follow-up (median; IQR: 4.25; 2.62- 4.69 years), two patients (6.6%) underwent repeat revascularization and one patient (3.3%) died due to MI. Overall primary endpoint rate was 9.9%. Conclusions: One-stage hybrid revascularization, on DAPT, is a feasible, safe and efficient way of achieving complete revascularization in selected patients. The complication rate is low and acceptable. Further randomized trials are required.